Energy metabolism of barren ground caribou ( Rangifer tarandus ) - McEwan, E. H. (Canadian Journal of Zoology, 1970)
The heat production of two caribou, during fasting, 91 kcal and 102 kcal/W 0.75 per 24 h, was 20 to 30% higher than the quoted interspecific mean of 70 kcal/W 0.75 per 24 h. The mean heat production values of two female caribou at the maintenance level of feeding were 107.0 kcal and 124.5 kcal/W 0.75 per 24 h.